2016
DOI: 10.1227/neu.0000000000001237
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow-up of the Prospective, Randomized, Controlled Trial of Coflex Interlaminar Stabilization vs Instrumented Fusion in Patients With Lumbar Stenosis

Abstract: CCS, composite clinical successCEC, clinical events committeeFDA, Food and Drug AdministrationIDE, investigational device exemptionILS, Coflex Interlaminar StabilizationODI, Oswestry Disability IndexSF-12, Short-Form 12VAS, visual analogue scalesZCQ, Zurich Claudication Questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 12 publications
1
26
0
1
Order By: Relevance
“…However, Coflex group had the advantages of less trauma, less intraoperative blood loss, early ambulation and shorter hospitalization days compared with fusion group. The results of the present study were consistent with those of previous researches [21][22][23][36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, Coflex group had the advantages of less trauma, less intraoperative blood loss, early ambulation and shorter hospitalization days compared with fusion group. The results of the present study were consistent with those of previous researches [21][22][23][36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…Since then, the device has been used in various degenerative spinal conditions [21][22][23][24][36][37][38]. Although it was initially developed as a motion-preserving alternative used to treat various lumbar degenerative disorders, long-term studies from Europe suggested that the subset of patients with spinal stenosis and Grade I spondylolisthesis experienced the most significant improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the ability of the ILS to provide relief of painful symptoms while maintaining segmental motion at both operated and adjacent levels is remarkable (7). In addition, the ILS maintains segmental stabilization without increasing angular and translational motion at the adjacent segments, thus maintaining the kinematics of the adjacent level.…”
mentioning
confidence: 95%
“…The ILS study reported by Bae et al (7) targeted patients with degenerative spondylolisthesis up to Meyerding grade I who were evaluated in sagittal plane translation on flexion-extension radiographs; however, they did not evaluate the scoliotic degeneration in the coronal plane. Considering that the mean change from preoperative to month 36 was only −0.30 mm in foraminal height after the ILS implant, the ILS might be also useful for the treatment © OSS Press Ltd. All rights reserved.…”
mentioning
confidence: 99%